IMPLEMENTASI METODE CENTRAL STEAM PADA PENINGKATAN PRODUKTIVITAS PENGUSAHA KECIL DI BERBAH, SLEMAN, YOGYAKARTA - Gunawan Madyono Putro; Prijoto Prijoto (Dharma: Jurnal Pengabdian Masyarakat, 2020)
Small entrepreneurs producing presto fish processed food in the village of Jogotirto Berbah experience problems in the fish processing process. The pressure tool used has not been optimal considering the length of time it takes to soften the fish and the inefficient fuel. This service program is designed to provide transfer of fish softening technology using the central steam method. Community service was carried out in the village of Jogotirto Berbah Sleman, involving 12 small entrepreneurs. The service provider provides training on using pressure tools with the central steam method for 2 sessions. Pengabdi provides pressure tools for the central steam method to small entrepreneurs and provides assistance for 5 months. The results of applying this method increased productivity by 50% and increased fuel efficiency by 40% so that the income of small entrepreneurs increased by 50% every month.